Common and Rare Genetic Risk Factors for Glaucoma - Wang, Ryan (Cold Spring Harb Perspect Med, 2014)
The characterization of genes responsible for glaucoma is the critical first step toward the development of gene-based diagnostic and screening tests, which could identify individuals at risk for disease before irreversible optic nerve damage occurs. Early-onset forms of glaucoma affecting children and young adults are typically inherited as Mendelian autosomal dominant or recessive traits whereas glaucoma affecting older adults has complex inheritance. In this report, we present a comprehensive overview of the genes and genomic regions contributing to inherited glaucoma.